Early evolutionary history of the flowering plant family Annonaceae: steady diversification and boreotropical geodispersal (2010)
Aim Rain forest?restricted plant families show disjunct distributions between the three major tropical regions: South America, Africa and Asia. Explaining these disjunctions has become an important challenge in biogeography. The pantropical plant family Annonaceae is used to test hypotheses that might explain diversification and distribution patterns in tropical biota: the museum hypothesis (low extinction leading to steady accumulation of species); and dispersal between Africa and Asia via Indian rafting versus boreotropical geodispersal. Location Tropics and boreotropics. Methods Molecular age estimates were calculated using a Bayesian approach based on 83% generic sampling representing all major lineages within the family, seven chloroplast markers and two fossil calibrations. An analysis of diversification was carried out, which included lineage?through?time (LTT) plots and the calculation of diversification rates for genera and major clades. Ancestral areas were reconstructed using a maximum likelihood approach that implements the dispersal–extinction–cladogenesis model. Results The LTT plots indicated a constant overall rate of diversification with low extinction rates for the family during the first 80?Ma of its existence. The highest diversification rates were inferred for several young genera such as Desmopsis , Uvariopsis and Unonopsis . A boreotropical migration route was supported over Indian rafting as the best fitting hypothesis to explain present?day distribution patterns within the family. Main conclusions Early diversification within Annonaceae fits the hypothesis of a museum model of tropical diversification, with an overall steady increase in lineages possibly due to low extinction rates. The present?day distribution of species within the two largest clades of Annonaceae is the result of two contrasting biogeographic histories. The ‘long?branch clade’ has been diversifying since the beginning of the Cenozoic and underwent numerous geodispersals via the boreotropics and several more recent long?distance dispersal events. In contrast, the ‘short?branch clade’ dispersed once into Asia via the boreotropics during the Early Miocene and further dispersal was limited.